Promoting Students’ English-Speaking Skill through Communicative Language Teaching (CLT) and Investigating Students’ Voices - Purnama, Dian; Aniuranti, Asfi; Wulandari, Yasinta; Haryani, Nur (Journal of Nusantara Education, 2026)
Speaking is an essential English skill, yet it can be troublesome for many learners. Every English teacher must implement teaching strategies to support the achievement of learning objectives in speaking classes. Speaking problems also appeared in MA Ma'arif NU Sains Al-Qur'an Sumbang. Therefore, the researchers conducted action research using Communicative Language Teaching (CLT) approach to boost the speaking skill of eleventh-grade students. This class was chosen because their speaking score was still low. Additionally, this investigation aims to explore students’ perceptions of CLT implemented. The action research was conducted through planning, acting, observing, and reflecting. The enhancement of speaking skill was measured through pre-test and post-test by calculating the average scores. Moreover, the students’ perceptions were explored through a questionnaire, and the data were analysed by calculating the percentage of each item. The test results demonstrated a notable increase in students’ speaking ability. In cycle 1, the average scores increased from 47.67 to 85.11.  Then, in Cycle 2, students’ English-speaking skill increased from 62.73 to 85.5. Additionally, based on the survey, the majority of students admitted that CLT exercises were enjoyable and useful in improving their speaking ability and confidence. The study shows that CLT exercises are successful in enhancing students' speaking skill, and it receives positive opinions from the students. Therefore, the findings of this study can be taken into account while utilising CLT to enhance students' English-speaking ability.